The influence of incontinence pads moisture at the loaded skin interface. Issue 3 (August 2019) - Bostan, Luciana E.; Worsley, Peter R.; Abbas, Shabira; Bader, Daniel L.
Abstract: Aim: Prolonged mechanical loading on soft tissues adjacent to bony prominences can lead to pressure ulcers. The presence of moisture at the skin interface will lower the tolerance to load. Absorbent pads manage moisture in individuals with incontinence, although their role in maintaining skin health is unknown. The present study investigated the effects of moist incontinence pads on skin physiology after periods of mechanical loading. Material and methods: Twelve healthy participants were recruited to evaluate a single incontinence pad design under three moisture conditions: 0% (dry), 50% and 100% fluid capacity. For each pad condition, pressure (9 kPa) or pressure in combination with shear (3 N) was applied to the sacrum, followed by a period of off-loading. Measures included trans -epidermal water loss (TEWL) and inflammatory biomarkers sampled at the skin interface. Results: Results revealed no change in TEWL in the loaded dry pad condition. By contrast, when the pads contained moisture, significant increases in TEWL were observed. These increases were reversed during off-loading. Inflammatory biomarkers, specifically IL-1α/total protein ratio, were up-regulated during dry pad loading, which recovered during off-loading. Loaded moist pads caused a significant increase in biomarkers, which remained elevated throughout the test period. Conclusion: The study revealed a marked compromise to stratum corneum integrity when the skin was exposed to moist incontinence pads in combination with mechanical loads. These physiological changes were largely reversed during off-loading. Incontinence pads provided some protection in the dry state, although more research is required to determine optimal clinical guidance for their use. Highlights: Dry incontinence pads provide some skin barrier protection during mechanical loading. Addition of moisture within the incontinence pads reduces the skin barrier function, with recovery during off-loading. Inflammatory cytokines levels increased after loading with moistened pads, with partial recovery during off-loading. Periods of pressure relief and careful management of moisture are critical for the maintenance of skin health. Introduction.